Realize digital transformation in higher education - Nida, Sofwatun; Murdianto; Setiyawan, Adhi; Sihono; Zefrizen, Arif (UIN Salatiga, 2025)
This article examines the implementation of a technology-based PAI learning model at UNU Yogyakarta to meet the demands of the digital era. This study aims to describe the strategy for integrating technology into PAI learning and analyze its contribution to the effectiveness of the learning process. The research method used is descriptive qualitative, with data collection techniques including in-depth interviews, participant observation, and documentation. The results of the study show that UNU Yogyakarta has successfully implemented an integrated digital learning model in the Islamic Religious Education (PAI) course . This system integrates the LMS platform, 2D and 3D-based animated video media for delivering materials , as well as digital application-based interactive quizzes for weekly formative evaluations. The use of digital technology has been shown to increase student learning engagement by 78%, based on the results observation of learning activities in the LMS, as well as improving critical thinking skills through case study-based assignments analyzed in online groups , finally the PAI learning technology integration model at UNU Yogyakarta is not only oriented towards technical aspects and learning efficiency, but also optimizes the strengthening of Islamic character.